Analysis of the influence of laser power on the microstructure and properties of a titanium alloy-reinforced boron carbide matrix composite (Ti6Al4V-B4C) - Ogunlana, Musibau O. (Strojniški vestnik, 2017)
Laser Metal Deposition (LMD) process is a means of producing metal composites with the aid of a laser beam, ejected onto the substrate with the participating powder and fused together after solidification. In this research work, Ti6Al4V alloy is fused with 20 wt % of B4C in order to form metal matrix composites (MMCs). Using the Ytterbium Fibre Laser System powdered at 3000 W, the laser powers were varied between 800 W and 2400 W while all other supporting process parameters were kept constant. The deposited Ti6Al4V- B4C composites were characterized through the surfacing microstructure, microhardness and dry sliding wear. The microstructural properties of the deposited samples were profound, with a Widmanstätten structure of alfa-Ti, beta-Ti and (alfa +beta) Ti phases. The microhardness tests revealed that the composites deposited with a laser power of 2000 W exhibited the highest hardness value and standard deviation of HV 445 +/- 61. Furthermore, characterisation revealed that the sample produced with the laser power of 800 W had the lowest wear loss and wear rate of 35.2 x 10 -3 mm3 and 6.42 x 10 -4 mm3/Nm. However, the motivation for this work is to improve the material properties of the Ti6Al4V alloy for surface engineering applications.
Keywords: kompoziti s kovinsko osnovo; kompoziti Ti6Al4V-B[sub]4C; lasersko nanašanje kovine; mikrostruktura; mikrotrdota; rentgenska difrakcija; suha drsna obraba